ANALISIS PRESTASI KERJA KARYAWAN DI PT. INDO PRIMA NUSANTARA MEDAN - RINA FRISKA B SIAHAAN; JESSIE SUSANA; WENY .; WILINNY .; WILLIAM VINCENT (LP2MTBM MAKARIOZ, 2019)
Job performance is the result of work obtained by someone when completing work that is charged to him. work performanceappraisal is a process for evaluating employee work results for their work. The benefits of performance appraisal (workperformance) are: as input for leaders to help and direct employees to improve their performance in the future and to carryout improvements and improvements in human resource management activities. There are two factors that affect workperformance, namely: individual factors consisting of effort (abilities), abilities (abilities), role / task perception, andenvironmental factors consisting of physical conditions, equipment, time, material, education, supervision, organizationaldesign, training, good luck. The informants studied were employees at PT. Indo Prima Nusantara Medan. The researchmethod used is a qualitative method where the data obtained is based on interviews with data sources used are primarydata. The formulation of the problem in this study,